Cost-benefit analysis of grid-connected wind–biogas hybrid energy production, by turbine capacity and site. (August 2015) - Mudasser, Muhammad; Yiridoe, Emmanuel K.; Corscadden, Kenneth
Abstract: The impacts of a recently launched community feed-in tariff (COMFIT) scheme on renewable energy production, with energy prices differentiated by renewable energy technology type, have not been adequately understood. The knowledge gap is addressed by applying the Hybrid Optimization Model for Electric Renewables (HOMER) decision tool to investigate the economic feasibility and effects of selected energy policy schemes on wind–biogas hybrid energy production, by taking into consideration geographic location (Greenwood, Sydney, Caribou Point), and wind turbine capacity (including 20, 35, and 50 kW). The biogas energy production component reflected a representative Nova Scotia, Canada dairy farm with 100 cows. Wind–biogas hybrid energy systems were generally not economically feasible without COMFIT scheme financial incentives. Locating the hybrid energy system one km away from a utility grid increased cost of energy produced by about 0.06 per kWh. Under current government COMFIT scheme with guaranteed energy prices, economic feasibility improved relative to a base scenario, with NPV per kWh increasing from -0.51 to 0.83 for a system with the 50 kW turbine at Caribou Point, compared with -0.51 to -0.14 for a similar 50 kW turbine at Sydney. Wind–biogas power production was economically viable under COMFIT scheme prices only for Caribou Point. Highlights: Analyzed alternative hybrid energy systems differentiated by capacity and site. HOMER model was applied to evaluate feasibility of wind–biogas power production. Renewable energy production was viable under COMFIT scheme prices for one site. Payback period ranged from 4 to 14 years, depending on hybrid power system and site. Wind speed was dominant driver of energy production and economic performance.